FINANCIAL MECHANISM OF CHARITABLE ORGANIZATIONS AND DIRECTIONS OF ITS IMPROVEMENT - M. E. Kosov (Вестник университета)
The functioning of charitable organizations in modern economic conditions requires significant financial resources. Analysis of financial aspects of Russian charitable organizations and development of recommendations for financial mechanism improvement are aims of the paper. The main problem of the financial mechanism functioning of the Russian charitable organizations is, that the legislation refers to charity, target assistance to specific people and organizations in limited period of time. The regulatory framework should encourage the emergence of sustainable charitable institutions – organizations, which are committed to long-term work. To expand their capabilities, it is advisable for charitable foundations to implement projects, related to commercial activities, all profits from which will be directed to the working capital of the Fund for purpose of redirecting to charity.